The Challenges of Microteaching and Teaching Readiness of Students at Islamic Higher Education - Abishev, Assylkhan R.; Ridha, Arif; Khalid, Essalihy (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2023)
Microteaching is an essential component in preparing prospective teachers, yet its implementation in several Islamic Higher Education still faces various structural and pedagogical challenges. This study aims to analyze current microteaching practices and identify the factors that influence students’ readiness in carrying out teaching practices. The research employed a qualitative method with a multi–case study approach. Data were collected through observations, interviews with lecturers and program chairs, and student questionnaires. The results show that microteaching classes were conducted without the support of a properly functioning laboratory, limiting students’ opportunities for systematic practice. The learning process remained dominated by lectures, with minimal pre-class assignments and reflection activities. Students exhibited low levels of engagement and weak self-directed learning skills, particularly in the areas of initiative, self-management, and self-evaluation. Interview data further revealed that students were still highly dependent on lecturer guidance, while partner schools reported a lack of student readiness during teaching practice. These findings indicate a discrepancy between curriculum requirements and students’ actual competencies. The study concludes that it is necessary to develop a microteaching model that integrates the principles of self-directed learning, expands opportunities for structured practice, and provides adequate learning facilities to enhance students’ teaching readiness in accordance with global professional standards.